Implementation of Culinary Arts Learning as a Medium for Developing Life Skills for Vocational High School Students in Tomohon City, North Sulawesi Province - Louisa Kandoli (Intelektualitas Jurnal Penelitian Lintas Keilmuan, 2025)
This study aims to examine and synthesise previous research on the implementation of culinary arts learning as a medium for developing students' life skills in vocational high schools (SMK) in Tomohon City, North Sulawesi Province. This study employed a literature review with a qualitative analysis approach. The literature search was conducted using Publish or Perish, a free platform integrated with Google Scholar. Keywords used included "learning," "life skills development," and article titles containing the word "category." The articles were selected based on their topic suitability and relevance to culinary arts learning and the development of vocational high school students' life skills. Furthermore, the selected articles were analysed qualitatively through theme grouping and synthesis of findings to formulate conclusions and recommendations applicable to vocational high schools in Tomohon City, North Sulawesi Province. The results indicate that culinary arts education is an effective medium for developing students' life skills through practical cooking experiences, integration of nutrition education, and the application of innovative learning models. This learning contributes to the development of personal, social, and vocational skills, such as time management, problem-solving, collaboration, and communication, which are essential for readiness for independent living and the world of work. In the context of vocational high schools (SMK) in Tomohon City, strengthening culinary arts education requires a holistic approach that integrates effective pedagogical strategies, local wisdom, industry partnerships, and innovative assessments, so that graduates possess relevant competencies and can compete in the culinary industry.